2020
DOI: 10.1111/adj.12756
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic osteosclerosis mimicry of a tooth: case report

Abstract: This report presents two cases of idiopathic osteosclerosis involving the maxilla and mandible which were identified as a buccally impacted canine and a retained root, respectively, on clinical and plain radiographical examinations. Both patients were females who presented with hypodontia. Radiographic evaluation revealed solitary well-defined radiopaque masses with thickened cortical border. Both patients were undergoing orthodontic treatment and one was planned for a surgical traction of unerupted tooth prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
2
9
0
1
Order By: Relevance
“…4,14,15 The location of DBI in the premolar and molar regions may be an indication that the DBI lesion represents root residues from primary molars that have been resorbed and replaced by sclerotic bone. 4,6,17 The location of the least number of DBIs found is also in accordance with several studies that have been carried out previously, namely in the incisive region. 5,8,15 Type 5 separately and type 4 apical are the two types of classification that are most commonly found compared to other types.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4,14,15 The location of DBI in the premolar and molar regions may be an indication that the DBI lesion represents root residues from primary molars that have been resorbed and replaced by sclerotic bone. 4,6,17 The location of the least number of DBIs found is also in accordance with several studies that have been carried out previously, namely in the incisive region. 5,8,15 Type 5 separately and type 4 apical are the two types of classification that are most commonly found compared to other types.…”
Section: Discussionsupporting
confidence: 91%
“…5 These lesions are more common in adults as well as in the female sex. 2,6 According to the study by Tolentino et al 7 , conducted on 20 samples, the description of DBI based on age, sex, size, shape, and location of the jaws and teeth differ from one individual to another.…”
Section: Introductionmentioning
confidence: 99%
“…They do not have any obvious etiological agents (12). They are usually asymptomatic, they do not cause cortical expansion, and they are detected incidentally on routine radiographs (13,14). The frequency of idiopathic osteosclerosis (3%) in this investigation falls within the range found by other studies, which vary from 1.96 to 7.6% (12,13,15,16).…”
Section: Discussionsupporting
confidence: 64%
“…They are usually asymptomatic, they do not cause cortical expansion and they are detected during routine radiological examination. 3,43 In studies conducted, the incidence of idiopathic osteosclerosis was found between 1.96 and 7.6%. [13][14][15][16] In our study, the incidence of idiopathic osteosclerosis was found to be 4.15%.…”
Section: Discussionmentioning
confidence: 99%